Clinical Metagenomic Next-Generation Sequencing for Diagnosis of Secondary Glaucoma in Patients With Cytomegalovirus-Induced Corneal Endotheliitis - Wu, Wei; Jiang, Hua; Zhang, Ying; Zhou, Yang; Bai, Guannan; Shen, Lingwei; Zhou, Hongwei; Chen, Xiangjun; Hu, Lidan (Frontiers in Microbiology, 2022)
Glaucoma is the second leading cause of blindness globally. Growing scientific evidence indicated that inflammation of the trabecular meshwork induced by corneal endotheliitis could lead to secondary glaucoma. Cytomegalovirus (CMV) has been identified as the most common herpes virus in corneal endotheliitis patients. Early detection is critical in preventing endothelial cell loss, and patient management should vary based on different pathological factors. However, routine culture and real-time polymerase chain reaction (qPCR) have difficult in distinguishing whether CMV, Varicella Zoster Virus (VZV) or Herpes Simplex Virus (HSV) causes endothiliitis. This may result in inappropriate treatment, which may prolong or aggravate the status of disease. We compared the sensitivity and specificity of qPCR and Metagenomic Next-Generation Sequencing (mNGS) in the aqueous humor of patients with suspected CMV endotheliitis in this study. Our results showed that four out of 11 (36.4%) of our patients were positive for CMV by qPCR, whereas mNGS had a 100% detection rate of CMV. Our findings implied that mNGS could be a useful diagnostic tool for CMV-induced endotheliitis.